2015
DOI: 10.1590/0103-8478cr20141690
|View full text |Cite
|
Sign up to set email alerts
|

Virus isolation in cell culture for confirmatory diagnostic of rabies in bovine specimens

Abstract: This study investigated the suitability of virus isolation (VI) in mouse neuroblastoma cells (N2A) and baby hamster kidney cells (BHK-21) as a confirmatory test for diagnosis of bovine rabies. Fourty-eight brain samples from cattle suspected of rabies were initially submitted to fluorescent antibody test (FAT) and mouse inoculation test (MIT RESUMO Este estudo investigou a sensibilidade do isolamento viral (VI) em células de neuroblastoma murino (N2A) e células de rim de hamster (BHK-21) como um teste confirma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
3
1
Order By: Relevance
“…and high sensitivity to this virus [20][21][22][23]. The optimal culture conditions found in this study differ slightly from the previous reports in relation to FBS supplementation [8,19,[22][23][24] and cell concentration [19,22,23,25,26], nonetheless were proven to obtain the best viral recovery rates.…”
Section: Plos Neglected Tropical Diseasescontrasting
confidence: 69%
“…and high sensitivity to this virus [20][21][22][23]. The optimal culture conditions found in this study differ slightly from the previous reports in relation to FBS supplementation [8,19,[22][23][24] and cell concentration [19,22,23,25,26], nonetheless were proven to obtain the best viral recovery rates.…”
Section: Plos Neglected Tropical Diseasescontrasting
confidence: 69%
“…We also compared the sensitivity of virus inoculation in cell culture as its use for rabies diagnosis has been reported as a reliable, cost‐effective, ethically preferable alternative to MIT (Fuoco et al., 2018; Kanitz et al., 2015; Madhusudana et al., 2010). RTCIT detected six positive samples (15%) that were negative or inconclusive in DFAT/MIT.…”
Section: Discussionmentioning
confidence: 99%
“…As such, MIT can be replaced by in vitro assays to confirm rabies diagnosis, which must be validated in the laboratory to ensure its accuracy. Studies have shown that inoculation of specific cell lines provides comparable results to MIT (Castilho, 2007;Corona et al, 2018;Kanitz et al, 2015). Such assays, collectively named Rabies Tissue Culture Infection Tests (RTCIT), require cell culture facilities (Corona et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In susceptible hosts, RABV is a primary neurotrophic virus that infects neurons in both the central and peripheral nervous systems [ 30 ]. In cell cultures, however, RABV can infect many types of cells, including those of non-neural origins, such as BHK-21 cells [ 1 , 12 , 21 ] and Vero cells [ 33 ]. A local RABV isolated from a rabid dog in Bali also replicated very well in BHK-21 cells.…”
Section: Discussionmentioning
confidence: 99%